1995
DOI: 10.1073/pnas.92.12.5361
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the human leukemia inhibitory factor (LIF) receptor by mitogen-activated protein kinase and the regulation of LIF receptor function by heterologous receptor activation.

Abstract: We used a bacterially expressed fusion protein containing the entire cytoplasmic domain of the human leukemia inhibitory factor (LIF) receptor to study its phosphorylation in response to LIF stimulation. The dose-and time-dependent relationships for phosphorylation of this construct in extracts of LIF-stimulated 3T3-L1 cells were superimposable with those for the stimulation of mitogen-activated protein kinase (MAPK). Indeed, phosphorylation of the cytoplasmic domain of the low-affinity LIF receptor a-subunit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
51
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 28 publications
1
51
0
Order By: Relevance
“…In contrast, comparable inhibition by CA-MKK3, CA-MKK6, and CA-MEK1 was seen when LIF, which signals through gp130 and a LIF-specific ␣-chain, was used. This is consistent with previously described inhibition of LIF signaling by ERKs (57) and confirms that CA-MEK1 is indeed active in our system. The inhibitory effect of CA-MEK1 or CA-MKK3 and CA-MKK6 was not detected when IFN-␥ was used, suggesting that these kinases do not nonspecifically block all Jak-Stat signaling, consistent with the lack of inhibition of IFN-␥ Stat1 activation (Fig.…”
Section: Role For P38 In Inhibition Of Il-6 Signalingsupporting
confidence: 81%
“…In contrast, comparable inhibition by CA-MKK3, CA-MKK6, and CA-MEK1 was seen when LIF, which signals through gp130 and a LIF-specific ␣-chain, was used. This is consistent with previously described inhibition of LIF signaling by ERKs (57) and confirms that CA-MEK1 is indeed active in our system. The inhibitory effect of CA-MEK1 or CA-MKK3 and CA-MKK6 was not detected when IFN-␥ was used, suggesting that these kinases do not nonspecifically block all Jak-Stat signaling, consistent with the lack of inhibition of IFN-␥ Stat1 activation (Fig.…”
Section: Role For P38 In Inhibition Of Il-6 Signalingsupporting
confidence: 81%
“…Plasmid Constructs-The expression vectors for the wild type and S1044A (S185A) mutant human LIFR␣ and chimeric G-CSFR-LIFR␣ in pDC302 have been described (10,22). Cytoplasmic domains of these receptors were modified by the addition of Myc epitope (EQKLI-SEEDLN) to the C terminus.…”
Section: Tissuementioning
confidence: 99%
“…Moreover, activation of ERK by insulin also increases LIFR␣ Ser 185 phosphorylation. It has been suggested that this modification may contribute to the modulation by insulin of cell responsiveness to LIF (22). However, the mechanism of this LIFR␣ regulation is unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The LIFR was found to contain 1097 amino acid residues (a 44-residue signal sequence, a 789-residue extracellular domain, a 26-residue transmembrane domain, and a 238-residue cytoplasmic domain) (6), and exhibits the characteristic structure of this receptor family, including two folding domains in the extracellular region and a Trp-Ser-X-Trp-Ser motif in the Cterminal (1). The LIFR heterodimerizes with gp130 to mediate intracellular signaling of interleukin-6 (IL-6) cytokine family members and is a substrate for mitogen-activated protein kinase (7)(8)(9)(10)(11)(12). The phenotype of the LIFR knockout mouse demonstrates that LIFR is essential for animal survival (13,14), whereby homozygote animals died within 24 h of birth (13,14), and severely affected tissues include placenta, bone, liver, and neurons (13).…”
mentioning
confidence: 99%